Aryl Hydrocarbon Receptor Signaling Synergizes with TLR/NF-κB-Signaling for Induction of IL-22 Through Canonical and Non-Canonical AhR Pathways - Ishihara, Yasuhiro; Kado, Sarah Y.; Bein, Keith J.; He, Yi; Pouraryan, Arshia A.; Urban, Angelika; Haarmann-Stemmann, Thomas; Sweeney, Colleen; Vogel, Christoph F. A. (Frontiers in Toxicology, 2022)
Interleukin 22 (IL-22) is critically involved in gut immunity and host defense and primarily produced by activated T cells. In different circumstances IL-22 may contribute to pathological conditions or act as a cancer promoting cytokine secreted by infiltrating immune cells. Here we show that bone marrow-derived macrophages (BMM) express and produce IL-22 after activation of the aryl hydrocarbon receptor (AhR) when cells are activated through the Toll-like receptor (TLR) family. The additional activation of AhR triggered a significant induction of IL-22 in TLR-activated BMM. Deletion and mutation constructs of the IL-22 promoter revealed that a consensus DRE and RelBAhRE binding element are necessary to mediate the synergistic effects of AhR and TLR ligands. Inhibitor studies and analysis of BMM derived from knockout mice confirmed that the synergistic induction of IL-22 by AhR and TLR ligands depend on the expression of AhR and Nuclear Factor-kappa B (NF-B) member RelB. The exposure to particulate matter (PM) collected from traffic related air pollution (TRAP) and wildfires activated AhR as well as NF-B signaling and significantly induced the expression of IL-22. In summary this study shows that simultaneous activation of the AhR and NF-B signaling pathways leads to synergistic and prolonged induction of IL-22 by integrating signals of the canonical and non-canonical AhR pathway.